Aneurysm or Tumor? Successful Endovascular Management of a Ruptured Cervical Internal Carotid Artery Aneurysms: A Case Report - Sikder, Md Shahidur Rahman; Subhan, Kazi Irfan; Akter, Nouroz; Sharif, Md Suzon; Hassan, Md Motassimul; Islam, Md Shafiqul (Bangladesh Journal of Neurosurgery, 2026)
Cervical internal carotid artery (ICA) aneurysms are rare, often mimicking neoplastic lesions and leading to misdiagnosis. Misguided surgical or biopsy interventions can result in catastrophic hemorrhage. We report a case of adolescent female with ruptured cervical ICA aneurysm initially misdiagnosed as neck tumor, which was successfully treated with endovascular occlusion techniques using N-butyl cyanoacrylate (NBCA) glue. This case highlight the importance of vascular imaging in suspicious cervical masses and reinforce the safety and efficacy of endovascular exclusion in selected cases Bang. J Neurosurgery 2024; 14(1): 66-69